Perspectives of Patients Receiving Telemedicine Services for Opioid Use Disorder Treatment: A Qualitative Analysis of User Experiences. Issue 6 (20th November 2022) - Sousa, Jessica L.; Raja, Pushpa; Huskamp, Haiden A.; Mehrotra, Ateev; Busch, Alisa B.; Barnett, Michael L.; Uscher-Pines, Lori
Abstract : Objective: Telemedicine for opioid use disorder (tele-OUD) has the potential to increase access to medications for OUD (MOUD). Fully virtual tele-OUD services, in which all care is provided via telemedicine, are increasingly common, yet few studies document the experiences of patients who use such services. Understanding patient perspectives is one of multiple considerations to inform the regulation and reimbursement of tele-OUD services. Methods: We conducted semi-structured interviews with 20 adults receiving care from one fully virtual tele-OUD service who had received 3 to 5 weeks of treatment. Analyses were conducted using an inductive and deductive approach informed by the modified Unified Theory of Acceptance and Use of Technology model. Results: Over three quarters of patients with past experience receiving in-person MOUD treatment described tele-OUD as more advantageous with its key strength being more patient centered. Over three quarters of patients said they felt tele-OUD helped to ameliorate social barriers to seeking treatment, and nearly all said they appreciated the speed at which they were able to initiate MOUD treatment via tele-OUD. Surprisingly, the pandemic was not among the factors that influenced patient interest in tele-OUD. Conclusions: Patients engaged in one fully virtual tele-OUD service described unique advantages of tele-OUD. More research is needed to determine the appropriateness of tele-OUD for people in various stages of recovery, and data on long-term treatment outcomes are needed to inform decisions regarding the regulation and reimbursement of fully virtual and hybrid care models for OUD.